Perlukah Mengatur Prinsip Exclusionary Rules of Evidence dalam RUU Hukum Acara Pidana? (Should We Regulate Exclusionary Rule Principle in the Criminal Procedural Bill?) - Marfuatul Latifah (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2021)
Illegal obtaining of evidence is still common in Indonesia. To prevent the repetition of this practice, the criminal procedural law recognizes the exclusionary rules of the evidence principle, which serve to eliminate evidence obtain illegally during trial examinations. This principle has become a worldwide common practice. This article examines the principles of exclusionary rules in the United States and the Netherlands. It examines whether the principles of exclusionary rules need to be regulated in Indonesian criminal procedural law. The exclusionary rules of evidence in the United States is regulated in the Mapp v Ohio, 367 U.S. 643 (1961), while in the Netherlands, it is regulated in Article 359a WvSv. In Indonesia, the existence of the principle of exclusionary rules is an interpretation of the phrase “valid evidence” so that evidence must be valid for both the type of evidence and the way it was obtained. To minimize illegal obtaining of evidence in Indonesia, the principle of the exclusionary rules needs to be regulated in the Criminal Procedural Bill to be effectively enforced in trials throughout Indonesia. In addition, the recognition for exclusionary rules in the Criminal Procedural Bill needs to delegate an authority to examine and validate evidence and determine what actions can be taken to illegal evidence. AbstrakPerolehan alat bukti secara ilegal masih sering ditemui di Indonesia. Untuk mencegah pengulangan praktik tersebut, hukum acara pidana mengenal prinsip the exclusionary rules of evidence (exclusionary rules) yang berfungsi untuk mengeliminasi alat bukti yang diperoleh secara ilegal dalam pemeriksaan persidangan. Penerapan exclusionary rules telah menjadi praktik yang umum dilakukan secara internasional. Artikel ini mengkaji pengaturan prinsip exclusionary rules di Amerika Serikat dan Belanda, serta mengkaji apakah prinsip exclusionary rules perlu diatur dalam hukum acara pidana Indonesia melalui RUU Hukum Acara Pidana. Artikel ini menggunakan metode pendekatan yuridis normatif yang kemudian dianalisis secara kualitatif. Pengaturan exclusionary rules di Amerika Serikat diatur dalam Putusan Mapp v. Ohio, 367 U.S. 643 (1961), sedangkan di Belanda diatur dalam Pasal 359a WvSv. Di Indonesia, keberadaan prinsip exclusionary rules merupakan tafsir dari frasa “alat bukti yang sah” sehingga alat bukti harus sah, baik jenis dan perolehannya. Untuk meminimalisasi perolehan bukti secara ilegal di Indonesia, prinsip exclusionary rules perlu diatur dalam batang tubuh RUU HAP agar dapat diberlakukan secara efektif dalam persidangan di seluruh Indonesia. Selain itu, pengaturan exclusionary rules pada RUU HAP perlu dilengkapi dengan pihak yang berwenang menguji dan mengesahkan alat bukti, serta menetapkan tindakan apa yang dapat diterapkan terhadap alat bukti yang tidak sah.